Meningkatkan Kompetensi Pendidik di Era Pembelajaran Abad 21 dengan Menjadi Guru Blogger - Nurmida Catherine Sitompul; Rufi'i Rufi'i; Ibut Priono Leksono; Heri Wahyu Rejeki (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2019)
Thoughtful Learning has formulated that in 21st Centuries, each students should have 4 C’s learning skill. The 4 C’s skill are critical thinking, creative thinking, communicating, and collaborating. These skills will help students becoming a problem solver. Method of 4 C’s in the classroom needs materials more variaties, contextual, from many resources and differences formats of datas (word, spreadsheed, ppt, video, animation). Materials for learning should be easy to acces in short time. Information Communication and Technology (ICT) can facilitates all these conditions. Generally almost all schools in cities have computers and internet acces but are used as information or school’s publication and do not use yet for learning. The purpose of this activity is to help teachers to create their own Blog to facilitating student’s learning. The result showed that all teachers can create a Blog for their Subject. The next activity is about how to integrating Blog into learning process.